Peelicious: A feasibility study on a candied citrus fruit byproduct - Denolong, Elaiza Marie R.; Domacena, Hazel Ann B.; Manansala, Aaliyah Mae D.; Micua, Remil A.; Ong Villa, Dominique Gabrielle L. 4 0 16; 5
EXECUTIVE SUMMARY: Name of the Company: The company name, Peelicious is a unique and catchy trade name that created from a portmanteau of the two words: peel and delicious. Peelicious is a witty and evocative name that creates an auditory image from the word peel to establish an association with the company's product as well as a sense of freshness. The company name is created using a zippy font creating a lively and energetic feeling to the name. This is complemented by a palette of clean white and bold black, this branding exudes sophistication and signals a fresh start-a symbol that what may seem like the end of a fruit's life cycle is, in fact, the beginning of a delightful culinary adventure. Peelicious Company's headquarters is located at 1307 Sagat Street, Paco, Manila. This location was strategically chosen as the area offers a small commercial space of 30 square meters, which is for the manufacturing and distribution operations of the company. This compact space is optimal for the initial business scale and can accommodate the production needs efficiently. Moreover, Sagat Street in Paco, Manila provides accessibility to various citrus fruit and raw material suppliers. Having proximity to these suppliers ensures a smooth and timely procurement process of raw materials, which is essential for maintaining consistent product quality and meeting customer demand. Additionally, the location's accessibility to commercial businesses and schools make it ideal hub to reach customers.
Feasibility Study: (BSBA major in Business Economics) - Pamantasan ng Lungsod ng Maynila, 2024
Keywords: 2 -- 0; 6; 20; 20; 2